Outcomes of neoadjuvant gemcitabine plus S‐1 and radiation therapy for borderline resectable pancreatic cancer. (21st November 2022) - Yabushita, Yasuhiro; Matsuyama, Ryusei; Miyake, Kentaro; Homma, Yuki; Kumamoto, Takafumi; Misumi, Toshihiro; Hata, Masaharu; Yamanaka, Shoji; Fujii, Satoshi; Endo, Itaru
Abstract: Background: The efficacy of multidisciplinary treatment, including neoadjuvant treatment, in borderline resectable pancreatic cancer (BRPC) remains unclear. We assessed the efficacy of neoadjuvant chemoradiotherapy with gemcitabine and tegafu/gimearcil/oteracil (S‐1) for BRPC. Methods: In a single center, nonrandomized prospective study, neoadjuvant chemoradiotherapy (NACRT) with gemcitabine plus S‐1 was administered for BRPC (no. B090312028) in 122 patients enrolled between 2009 and 2015. Gemcitabine plus S‐1 comprised gemcitabine on days 8 and 15, and daily S‐1 on days 1‐14. After two courses of gemcitabine plus S‐1, 30 Gy radiotherapy was administered in 10 fractions with S‐1. Results: Eighty‐four and 38 patients had BR‐PV and BR‐A, respectively. No deaths occurred during NACRT. Ninety‐four patients (77%) underwent resection with curative intent. R0 resection was performed in 91% of resected cases. Patients who underwent post‐NACRT resection had better overall survival than did patients without resection (mean survival time [MST]: 24.7 vs 9.6 months, 5‐year‐survival rate (5 years): 30.3% vs 0%, P < .001). Adjuvant chemotherapy was administered in 73% of patients. MST and 5‐year survival rate of the patients treated with NACRT followed by resection and adjuvant chemotherapy were 29.6 months and 34.3%, respectively. Conclusions: Neoadjuvant chemoradiotherapy with gemcitabine and S‐1 can be safely administered in BRPC and may require adjuvant chemotherapy. Clinical Trial Registration Number: This study was registered with the University Hospital Medical Information Network‐Clinical Trials Registry (UMIN‐CTR) UMIN000006782. Abstract : Yabushita and colleagues investigated the usefulness of neoadjuvant gemcitabine plus S‐1 and radiation therapy in improving the outcomes of patients with borderline resectable pancreatic cancer. They concluded that neoadjuvant chemoradiotherapy was safe and contributed to prolonging the prognosis, but they suggest that postoperative adjuvant chemotherapy remains important as well.